“PARA PRESIDENTE, VOTE NA GENTE” As personalidades presentes nos programas do PT e PSDB veiculados no horário eleitoral de 2002, 2006 e 2010. - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
The purpose of this paper is to analyze the personalities that appear in the first round of the election campaigns for the presidency of Brazil taken from the political free advertising time (HGPE) of the two major brazilian parties, PT and PSDB, in the years of 2002, 2006, and 2010. The choice for the first round was made because that is the time in which each party tries to get more attention than the others. At this stage, all parties compete against each other and the two parties that get more attention from the voters reach the second round. This happens on the assumption that candidates tend to approach the same issues during the TV programs and the personal factors can generate greater prominence for them. One of the strategies used is the presence of people of political and social prestige appearing on HGPE to express support for the candidate. Some of these people can be called patrons, due to their characteristics. This research intends to see which personalities appeared in the television campaign in the three elections chosen. The study of a specific figure within the campaign on television is justified because it is believed that the personal aspects of the candidates and the people who participate in the campaign tend to influence the voters' choice, since the thematic elements are not the only factors that help the voting decision. The main hypothesis is that PT and PSDB use the patron in different ways. Also, there is the strategy used to build the image of the candidate, which aims to qualify him/her as the best voting option by showing the voters their personal attributes. The methodology is based on discourse analysis studies by Charaudeau (2008), supported by quantitative method as a way to complement the analysis. In general, research has shown that there is a strong presence of political figures and social programs in the three years, but only two personalities can be consdered patrons. In 2002, there was a strong presence of artists in the PSDB programs, but none of them can be considered a social patron. 2006 was the year in which political figures appeared the most in the PSDB programs, but only as means of support. Only in 2010 appears the type of electoral patron in HGPE, such as Luiz Inácio Lula da Silva, on Dilma Rousseff's programs.
Keywords: campanha presidencial; patrono; horário eleitoral; presidential campaign; patron; election time; CNPQ::CIENCIAS SOCIAIS APLICADAS